2020
DOI: 10.3389/fnhum.2020.00141
|View full text |Cite
|
Sign up to set email alerts
|

Neural Dynamic Responses of Monetary and Social Reward Processes in Adolescents

Abstract: Adolescence is an essential developmental period characterized by reward-related processes. The current study investigated the development of monetary and social reward processes in adolescents compared with that in children and adults; furthermore, it assessed whether adolescents had different levels of sensitivity to various types of rewards. Two adapted incentive delay tasks were employed for each participant, and event-related potentials (ERPs) were recorded. The behavioral results showed that both monetar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 122 publications
(189 reference statements)
1
20
0
Order By: Relevance
“…More precisely, the P2 amplitude has been related to the emotional evaluation of rewards 27,28 . This has been confirmed in recent studies across different experimental paradigms [29][30][31] . The P2 amplitude has also been related to other processes such as feature detection and allocation of attentional resources [32][33][34] as well as emotional evaluation of stimuli 35,36 .…”
supporting
confidence: 75%
“…More precisely, the P2 amplitude has been related to the emotional evaluation of rewards 27,28 . This has been confirmed in recent studies across different experimental paradigms [29][30][31] . The P2 amplitude has also been related to other processes such as feature detection and allocation of attentional resources [32][33][34] as well as emotional evaluation of stimuli 35,36 .…”
supporting
confidence: 75%
“…Several studies have compared the neural responses to social and monetary rewards ( Demurie et al, 2011 , Demurie et al, 2012 , Ethridge et al, 2017 , Ethridge and Weinberg, 2018 , Izuma et al, 2008 , Lin et al, 2012 , Rademacher et al, 2010 , Saxe and Haushofer, 2008 , Wang et al, 2017 , Wang et al, 2020 ). We previously investigated how social and monetary rewards affected a simple two-choice process (a triangle with left hand response, a square with right hand response) in children, adolescents, and adults ( Wang et al, 2017 , Wang et al, 2020 ). We found that both monetary and social rewards could speed up participants’ responses, and their reaction time (RT) decreased with the enhancement of the reward magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have compared directly social and nonsocial reward responses report that adolescents rated social rewards as more subjectively motivating than monetary rewards (Wang et al., 2017). In the same paradigm, electrophysiological signals of response speed and cognitive control correlated only under conditions of social reward, interpreted as increased sensitivity and attentional engagement to social reward cues in the adolescent group (Wang et al., 2020). Longitudinal neuroimaging research on effects of incentives on inhibitory control show substantial individual differences in terms of whether incentives will improve or impair performance, and the brain circuitry underpinning performance is shown to follow a protracted developmental trajectory into adulthood (Paulsen et al., 2015).…”
Section: Discussionmentioning
confidence: 99%